Effect of Workplace Violence and Psychological Stress Responses on Medical-Surgical Nurses' Medication Intake. Issue 2 (June 2021) - Havaei, Farinaz; MacPhee, Maura
Background: Workplace violence is a prevalent phenomenon in the health-care sector globally, but few studies have examined its impact on nurses' use of prescribed and/or over-the-counter medications to manage signs and symptoms. Purpose: The purpose of this study was to examine the direct and indirect effect of workplace violence, through the pathway of psychological stress responses, on nurses' frequencies of medication intake. An occupational stress and health outcomes model was tested in this study. Methods: A secondary analysis of cross-sectional survey data from 551 medical-surgical nurses in British Columbia was conducted. Both emotional and physical workplace violence were examined. Emotional exhaustion and posttraumatic stress disorder were psychological stress responses to workplace violence. Results: Emotional and physical violence from patients and/or families were the most prevalent sources of workplace violence. Physical violence and psychological stress responses increased the frequency of medication intake after controlling for nurse characteristics. Emotional violence was not related to medication intake over and above the effect of psychological stress responses. Physical and emotional violence elicited psychological stress responses resulting in increased medication use. Conclusion: Workplace violence triggers psychological stress responses with adverse outcomes on nurses' health and well-being.